Quantum Dot-Driven Stabilization of Liquid-Crystalline Blue Phases - Cordoyiannis, George; Lavrič, Marta; Trček, Maja; Tzitzios, Vasileios; Lelidis, Ioannis; Nounesis, George; Daniel, Matej; Kutnjak, Zdravko (Frontiers in Physics, 2020)
Liquid crystals hosting nanoparticles comprise a fascinating research field, ranging from fundamental aspects of phase transitions to applications in optics and photonics. Liquid-crystalline phases exhibit topological defects that can be used for self-assembly of nanoparticles in periodical arrays and, at the same time, the nanoparticles can increase the stability range of liquid-crystalline phases. This has been experimentally demonstrated over the past few years in the case of blue phases that are present in some strongly chiral liquid crystals. Experimental results in quantum dot-driven blue phase stabilization are presented here by means of high-resolution calorimetry and polarizing optical microscopy. It is demonstrated that quantum-dots essentially stabilize the macroscopically amorphous blue phase III. There are discussed similarities and differences between the effects of spherical and anisotropic nanoparticles on blue phase stabilization; moreover, future prospects and trends in the field are addressed.